Modern Parenting In Delhi Ncr: Trends, Challenges And Transitions - Butta, Prerna; Chaudhary, Nidhi (Journal of Neonatal Surgery, 2025)
Parenting in urban India has undergone significant transformation due to rapid socio-economic change, globalization, and technological advancement. This review paper examines the evolving nature of modern parenting in the Delhi National Capital Region (NCR), with a specific focus on children in middle childhood (6–12 years). Drawing on secondary data from recent empirical studies and theoretical literature, the paper explores the transition from traditional collectivist parenting practices to contemporary child-centric and autonomy-supportive approaches. The study highlights emerging parenting trends such as intensive parenting, digital parenting, and conscious parenting, while also identifying the persistence of traditional values, including academic prioritization and respect for authority. It critically analyzes major parenting styles, emphasizing the increasing adoption of authoritative parenting in urban contexts due to its strong association with children’s socio-emotional and cognitive development. The paper is theoretically grounded in key developmental frameworks, providing a multidimensional understanding of parenting practices and their influence on child development. Furthermore, the study examines the role of cultural values, globalization, changing family structures, and digital technologies in shaping parenting behaviors in Delhi NCR. The findings indicate that while modern parenting offers opportunities for enhanced child development through informed and responsive practices, it also presents challenges such as work–life imbalance, digital dependency, reduced familial support, and heightened academic pressure. The paper concludes that effective parenting in contemporary urban settings requires a balanced integration of traditional values and modern approaches, with strong emphasis on emotional responsiveness, consistency, and adaptive strategies. The study contributes to the growing discourse on parenting in urban India and offers directions for future research and policy interventions